DOI: 10.31274/rtd-180813-11463
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic system models and measurements

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…At any point B on the actual transducer, the sound pressure pe radiated by the circular section can be calculated by Equation (1); furthermore, by integrating the sound pressure pe on the entire surface of the transducer [14,15,16], the average echo sound pressure truePs¯ can be obtained approximately by Equation (3):p¯normals(normalR,sans-serifθ)=(sans-serifπ(normald/2)2sans-serifλnormalR)[2J1(normalk(d2)sinsans-serifθ)normalk(d2)sinsans-serifθ]·truepr¯·sans-serifπnormala2 where λ is the wave length of ultrasonic waves in a medium, a is the transducer radius, k is the wave number, J1 is the first order Bessel function, θ is the angle between R and the Z-axis, Rw is the reflection coefficient at the inner surface of the wall, and truepr¯=p0esans-serifαnormalLRw·4a2/d2.…”
Section: Echo Sound Pressure Calculation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…At any point B on the actual transducer, the sound pressure pe radiated by the circular section can be calculated by Equation (1); furthermore, by integrating the sound pressure pe on the entire surface of the transducer [14,15,16], the average echo sound pressure truePs¯ can be obtained approximately by Equation (3):p¯normals(normalR,sans-serifθ)=(sans-serifπ(normald/2)2sans-serifλnormalR)[2J1(normalk(d2)sinsans-serifθ)normalk(d2)sinsans-serifθ]·truepr¯·sans-serifπnormala2 where λ is the wave length of ultrasonic waves in a medium, a is the transducer radius, k is the wave number, J1 is the first order Bessel function, θ is the angle between R and the Z-axis, Rw is the reflection coefficient at the inner surface of the wall, and truepr¯=p0esans-serifαnormalLRw·4a2/d2.…”
Section: Echo Sound Pressure Calculation Modelmentioning
confidence: 99%
“…In Figure 5 , the circular section at the inner surface can be approximately regarded as a round transmitting transducer whose average initial pressure is . At any point B on the actual transducer, the sound pressure radiated by the circular section can be calculated by Equation (1); furthermore, by integrating the sound pressure on the entire surface of the transducer [ 14 , 15 , 16 ], the average echo sound pressure can be obtained approximately by Equation (3): where is the wave length of ultrasonic waves in a medium, is the transducer radius, is the wave number, is the first order Bessel function, is the angle between R and the Z-axis, is the reflection coefficient at the inner surface of the wall, and .…”
Section: Echo Sound Pressure Calculation Modelmentioning
confidence: 99%
“…The computational inefficiency of numerical methods has led many authors to consider approximate wave scattering models such as elastodynamic ray theory [66,67], low frequency expansions [68,69], and the Kirchhoff and Born approximations [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. The Kirchhoff approximation in particular has been found to be very useful and widely studied in the literature [70][71][72][73][74].…”
Section: Scattering Modelsmentioning
confidence: 99%
“…However, experiments of Gray [62] and recent experimental benchmark studies [75] have shown that the Kirchhoff approximation accurately predicts the pulse-echo response of a circular crack at relatively high angles from normal incidence. Also, recent model-based benchmark studies [77][78] have suggested that the Kirchhoff approximation can work well at much lower frequencies/sizes where kb »1 is violated. In Chapter 5 it will be shown that this apparent disagreement of earlier and more recent studies on when the Kirchhoff approximation is valid can be explained by the fact that the accuracy of the Kirchhoff approximation depends on both the non-dimensional wave number kb and the bandwidth of the system.…”
Section: Scattering Modelsmentioning
confidence: 99%